A review of petroleum emulsions and recent progress on water-in-crude oil emulsions stabilized by natural surfactants and solids - Umar, A.A. (Elsevier B.V., 2018)
During production of conventional as well as heavy oils, emulsions occur at well bore, in pipelines, and at surface facilities. As the production time of the oil wells increases, there will be an increased coproduction of oil and water in the form of emulsions. These emulsions are undesirable because they result in high pressure drop due to their high viscosity. They also cause serious corrosion problems due to presence of chlorides dissolved in water. These emulsions must be treated to meet production and transportation requirements, and to maximize the overall profitability of the crude oil production. Apart from the undesirable emulsions, the petroleum industry is witnessing a surge in the application of emulsions for beneficial processes. Both cases would be discussed in this review. This subject has experienced an extensive research over the years, with highly complicated theories regarding the phenomena involved in its formation (emulsification) and breaking (demulsification). Crude oils, irrespective of their origin, contain certain components or characteristics which tend to make them emulsifiable. These crude oil components are referred to as emulsifiers, and they vary so widely with the nature of the crude oil. The natural interfacially active components responsible for emulsion stability undoubtedly come from the resin and asphaltenes of the crude oil. However, the presence of other solids like crystalline waxes, clays, corrosion products and mineral scales may lead to the formation of very stable water-in-oil (w/o) emulsions. The nature of these particles controls the type as well as the stability of emulsions produced. Apart from the natural emulsifiers, chemical enhanced oil recovery (EOR) techniques have been reported to produce stable w/o and o/w emulsions. It is believed that the alkali, surfactant and polymers used in these techniques are responsible for these stable emulsions. When they form, these emulsions increase pumping costs, heighten the chances of pipeline and equipment erosion, corrosion rate, scaling and lower the produced oil API gravity. These emulsions have to be treated to remove the dispersed water and accompanying inorganic salts in order to meet market specifications, transportation requirement and to reduce corrosion and catalyst poisoning in downstream processing. Despite the huge and concerted efforts by researchers from the academia and the petroleum industry, there are few fundamental and applied investigations into the roles of native solids in combination to natural emulsifiers on the stabilization of petroleum emulsions. This paper presents a comprehensive overview of the progress made in the field of petroleum emulsions, principally the roles of particles in combination to asphaltene and resin in stabilizing w/o emulsions. The study also charts a way for emulsions studies that could lead to an effective demulsification via thorough characterizations of the solids believed to the enhancers of emulsion stability in order to tailor demulsifiers based on the characteristics of such emulsifiers. Â© 2018 Elsevier B.V.